Tinjauan dan Perlindungan Hukum Terhadap Hilangnya Sertifikat Hak Milik Atas Tanah - Fatahillah Al Balad; Husein Manalu (CV. ULIL ALBAB CORP, 2024)
This research aims to analyze the procedures and legal protection against the loss of land ownership certificates. This research includes empirical juridical research, the juridical approach in this research means that this research is viewed from the perspective of legal science. Meanwhile, what is meant by an empirical approach is research that aims to gain knowledge about the relationship between law and society and the factors that influence the implementation of law in society. This approach is implemented by conducting direct research from respondents and sources in the field with the aim of collecting objective data, which is referred to as primary data. This research was conducted at the Bekasi Regency Land Office with Mr Yasir who was one of the victims of losing his certificate in the Bekasi Regency area, Cibatu Village, South Cikarang District,